Shoseiryuto Ameliorated TDI-Induced Allergic Rhinitis by Suppressing IL-33 Release from Nasal Epithelial Cells - Manabu Kitano; Seiya Fukuoka; Naoki Adachi; Tadashi Hisamitsu; Masataka Sunagawa (Pharmaceutics, 2022)
Toluene diisocyanate (TDI) is a major cause of occupational asthma and rhinitis. Shoseiryuto (SST) is one of the traditional herbal medicines (Kampo medicine) and has long been used as a natural medicine for allergic diseases such as allergic rhinitis (AR) and asthma. Recent studies have shown that the expression and release of IL-33, which regulates the TH2 cytokine response in epithelial cells, is an important step in developing the inflammatory response of the nasal mucosa. In this study, we investigated whether SST may ameliorate the TDI-induced AR-related symptoms in rats and inhibit IL-33 release from nasal epithelial cells. An AR rat model was generated by sensitization and induction with TDI. SST was administered during the sensitization period. AR-related symptoms in rats were evaluated, and IL-33 release was measured both in vivo and in vitro. SST suppressed symptoms appearing in TDI-induced AR model rats, such as elevated serum histamine and IL-33 levels in nasal lavage fluid (NLF)/serum, which were suppressed by SST administration. TDI-induced IL-33 release from the nasal epithelial cell nuclei was also observed and suppressed in SST-treated rats and cultured nasal epithelial cells. These results suggest that SST ameliorates the symptoms of TDI-induced AR at least partially by inhibiting IL-33 release from nasal epithelial cells.